The journal of Economic perspectives (American Economic Association, 1999)
The Journal of Economic Perspectives fills a gap between the general interest press and most academic economics journals. It offers policymakers, educators, students, and economic practitioners well-written and well-chosen analytical essays that focus the lens of economic reasoning on topics across the social sciences. It draws attention to newly important topics, not yet covered in the referred journals; informs and shapes the debate on public issues; provides readings for classroom use; and addresses matters relating to the economics profession. Most papers are solicited, from experts in the field. This journal--the most accessible of all seven American Economic Association academic journals--exposes the power, utility, and beauty of clear economic insight.